History Reborn in Free Competition : The Czech and Slovak Post-communist Transitions and Their Dominant Historical Narratives - Sniegoň, Tomáš (Dějiny – teorie – kritika, 2009)
Two of the four historical narratives presented here, the Czech national-liberal narrative and the Slovak national-European narrative, imbue Czech and Slovak history with national and democratic meaning, by using history to legitimize future aims in these areas. The two remaining historical narratives, the Communist and the Slovak national-Catholic, with their way of using history, take an expressly confrontational stance on values called ‘politically liberal’, though in their renewed versions from the 1990s they no longer call outright for totalitarian power. All four narratives, however, work with their own nations and histories as monolithic categories, and consequently have problems answering questions that do not fit into their conceptions of the search for their own meanings of Czech or Slovak history. In their endeavours to define new post-Communist values, the main actors have failed to abandon or even to cast doubt on the ethnically determined national framework.